2021
DOI: 10.1093/jamia/ocab074
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of event notification following discharge to improve geriatric care: qualitative interviews of care team members from a 2-site cluster randomized trial

Abstract: Objective To assess primary care teams’ perceptions of a health information exchange (HIE) event notification intervention for geriatric patients in 2 Veterans Health Administration (VHA) medical centers. Materials and Methods We conducted a qualitative evaluation of an event notification alerting primary care teams to non-VHA hospital admissions and emergency department visits. Data were collected through semistructured inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In our prior work, we showed that HIE notification of acute care encounters improves primary care team follow-up as compared to a no-notification control group, 47 and that primary care team members found the notifications helpful for filling information gaps and supporting timely follow-up. 8 Others have shown a 2.9% reduction in 30day readmissions associated with HIE electronic notifications. 23 Though the comparison condition in this study, electronic notifications of outside encounters is not yet a standard of care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our prior work, we showed that HIE notification of acute care encounters improves primary care team follow-up as compared to a no-notification control group, 47 and that primary care team members found the notifications helpful for filling information gaps and supporting timely follow-up. 8 Others have shown a 2.9% reduction in 30day readmissions associated with HIE electronic notifications. 23 Though the comparison condition in this study, electronic notifications of outside encounters is not yet a standard of care.…”
Section: Discussionmentioning
confidence: 99%
“…7 VA providers are often not aware of non-VA encounters until notified by non-VA providers, patients, or families. 8 This is likely one reason dual VA and non-VA system use is associated with higher hospital admission and readmission rates and greater adverse events, 9,10 in particular for older veterans. 5,11,12 Health information exchange (HIE) allows health-care providers and patients to access and securely share medical information electronically.…”
Section: Introductionmentioning
confidence: 99%
“…Even when information is shared between home health and medical providers, primary care teams may not act upon it. Several studies have found primary care physicians frequently did not respond to communication from home health nurses (Norton et al, 2021; Smith et al, 2016), and medical teams may view outside notifications (e.g., notification of an acute episode) as an additional burden in their already full schedules (Franzosa et al, 2021; Vest & Ancker, 2017). Effectively sharing information will require workflows that allow primary care teams to efficiently act on information, identifying the team members who need to share and receive information and the ideal timing and content.…”
Section: Discussionmentioning
confidence: 99%
“…The CFIR synthesizes constructs from multiple theories into a robust framework and has been found effective for guiding the successful implementation of programmatic innovations in numerous health care domains. 11–15 This framework, first published in 2009 and since updated, features a list of constructs categorized into five domains (Innovation Characteristics, Outer Setting, Inner Setting, Individual Characteristics, and Process) and provides a way to systematically assess barriers and facilitators to either prepare for or assess the implementation of an innovation. 16…”
Section: Methodsmentioning
confidence: 99%